A Review of Customer Satisfaction with a Special Emphasis on Healthcare (British Journal of Multidisciplinary and Advanced Studies, 2025)
Customer satisfaction is an important construct to enhance the quality of healthcare services. The purpose of assessing customer satisfaction is to analyse the multidimensional interactions from the perspective of the customer so that such information can be used to enhance quality of healthcare. The aim of this paper was to review the literature and the theoretical frameworks of customer satisfaction with a special emphasis on healthcare. This review focussed on the concept of satisfaction, explained the models of satisfaction, types of satisfaction, dimensions and determinants of satisfaction and predictors of satisfaction.